Preventive and Curative Measures to Combat Online Gambling from the Perspective of the Qur'an and Hadith - Putra, Dimas Pradana; Afifudin, Ridho; Masuwd, Mowafg Abrahem (Postgraduate Program, State Islamic Institute (IAIN) Kediri, Indonesia, 2025)
This study aims to analyze preventive and curative efforts in addressing online gambling based on the perspective of the Qur'an and Hadith. Online gambling is a rapidly growing social phenomenon in the digital age, which not only hurts individuals but also on society in general, economically, socially and morally. This activity is becoming increasingly prevalent and has a significant impact on users and addicts because it is easily accessible to anyone. In Islam, all forms of gambling, including online gambling, are prohibited because they can destroy the order of people's lives. This study uses a qualitative-descriptive approach with a literature review method (library research) to explore Islamic views on gambling. The study concludes that preventive and curative approaches derived from the Qur'an and Hadith are highly relevant for addressing online gambling in the modern era. The proper implementation of these Islamic teachings is expected to reduce gambling rates and build a more moral, moderate, and religious society.